Applying Artificial Intelligence Techniques in Accounting to Improve the Quality of Financial Reports: A Survey of The Opinions of a Sample of Academics, And Professionals in Iraq - Hasan Khlaif , Murtadha (Iraqi Journal for Administrative Sciences, 2026)
The primary objective of applying artificial intelligence (AI) technologies, as an information technology component, is to enhance the quality of financial reporting. This is achieved through AI's advanced capabilities in classifying, processing, and analyzing financial data with high accuracy and speed. These technologies contribute to the early detection of potential risks, as well as their role in continuously verifying the integrity of financial data and implementing precise and effective control systems for financial operations. This, in turn, helps reduce the likelihood of manipulation, forgery, and financial fraud. Furthermore, AI technologies possess advanced predictive capabilities that support decision-making processes. This, in turn, enhances the confidence of decision-makers by providing high-quality financial reports supported by AI-based analytics, thereby increasing transparency in handling financial data. The research comprised two main aspects: a theoretical framework and an applied framework. The research employed a descriptive-analytical approach to analyze variables and test hypotheses. To collect data, a questionnaire was used, distributed to a sample of accountants and auditors as the primary group, in addition to a sample of programmers. The number of valid responses for analysis was 121. The SmartPLS statistical software was used to analyze the data and test the research model. The research results indicated a significant positive impact of artificial intelligence technologies (machine learning, deep learning, neural networks, expert systems, and the Internet of Things) on improving the quality of financial reports.